Optimasi Kualitas Jaringan WLAN Berdasarkan Coverage Area dan Jumlah Pengguna di Fakultas Teknologi Industri UNISSULA - Jatmiko, Destra Kurniatama; Jati, Budi Pramono; Hapsari, Jenny Putri (Universitas Semarang, 2021)
WLAN is a wireless telecommunications network in the process of distributing data or information. This network is easier and economical to build because without having to do the design of cable lines and no need for cables as devices. In the main building of the Faculty of Industrial Technology UNISSULA already has a WLAN network, but there are blankspots in several areas. The layout and number of Access Points (AP) greatly affect the quality of the WLAN signal, besides the number of users. Optimization is done by comparing the number of AP exiting with the number of APs based on the coverage area and number of users. The parameters used for network quality are signal strength more than -75 dBm and Signal to Noise Ratio (SNR) of more than 25 dB. Retrieval of existing network quality data with walktest method using the Ekahau Site Survey software. The quality of signal strength and SNR based on the coverage area is calculated using the COST 231 Multiwall method, while those based on the number of users are calculated using the ratio of Airtime per Device (APD) to Number of Device (NoD). The next step, simulating the AP layout using the Ekahau Site Survey software. The research concluded that each floor only requires 2 pieces AP. The percentage value of signal strength> -75 dBm after optimization is 86%, 89.8%, and 87.4% for floors 1, 2, and 3 respectively. While the SNR percentage values> 25 dB after optimization are 81.1%, 86.3%, and 84.5% for floors 1, 2, and 3 respectively.